ATTITUDES AND MAINTENANCE EFFORTS OF INDONESIAN MECHANICAL ENGINEERING STUDENTS TOWARD ACQUIRED, LEARNED, AND USED LANGUAGES - Retnowaty Retnowaty (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
This study investigates the language attitudes and maintenance efforts of Indonesian mechanical engineering students toward three types of languages: the national language (Indonesian), the global language (English), and local/heritage languages. It explores how students evaluate and sustain their multilingual repertoire within the context of higher education. Employing an explanatory sequential mixed-methods design, data were collected through questionnaires (n = 43) and semi-structured interviews with students from a private university in Balikpapan. The findings reveal that students hold generally positive attitudes toward all three language types, although with different levels of emotional, instrumental, and functional engagement. Indonesian is the most emotionally and functionally dominant language, actively used in academic and social contexts. These patterns reflect a hierarchical model of language maintenance shaped by pragmatic utility, social capital, and symbolic value. This study contributes to understanding multilingual practices in technical disciplines and calls for responsive educational strategies to support communicative English learning, academic Indonesian usage, and community-based local language revitalization.